2021
DOI: 10.1161/jaha.120.020559
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmia Risk During the 2016 US Presidential Election: The Cost of Stressful Politics

Abstract: Background Anger and extreme stress can trigger potentially fatal cardiovascular events in susceptible people. Political elections, such as the 2016 US presidential election, are significant stressors. Whether they can trigger cardiac arrhythmias is unknown. Methods and Results In this retrospective case‐crossover study, we linked cardiac device data, electronic health records, and historic voter registration records from 2436 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Results from this study are consistent with other studies surrounding the 2016 election. 6 , 7 Rosman and colleagues 7 studied patients in 2 health care centers in North Carolina, and they found a 77% higher risk of cardiac arrhythmia in the 6 weeks after the 2016 election compared with a similar period before the election. Results were consistent by age group, sex, and race and ethnicity, and the authors also reported no differences by political affiliation or political concordance or discordance—although they note small sample sizes as the potential limitation to some of these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from this study are consistent with other studies surrounding the 2016 election. 6 , 7 Rosman and colleagues 7 studied patients in 2 health care centers in North Carolina, and they found a 77% higher risk of cardiac arrhythmia in the 6 weeks after the 2016 election compared with a similar period before the election. Results were consistent by age group, sex, and race and ethnicity, and the authors also reported no differences by political affiliation or political concordance or discordance—although they note small sample sizes as the potential limitation to some of these findings.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Other studies have similarly presented evidence of cardiovascular and noncardiovascular adverse outcomes associated with political stress and, more specifically, the 2016 presidential election. 7 , 8 , 9 The aim of the current study was to replicate and expand on findings from our prior study of the 2016 presidential election that was limited to the Southern California population by examining hospitalizations for acute CVD around the 2020 presidential election among adults in KPSC and Kaiser Permanente Northern California (KPNC), 2 large integrated health care delivery systems that provide comprehensive care for more than 9 million persons.…”
Section: Introductionmentioning
confidence: 97%
“…In previous studies, major sociopolitical events were associated with significant changes in self‐rated health status, mental health, and cortisol levels (Brown et al, 2021; Hoyt et al, 2018; Malat et al, 2011). Recent data also suggests that incidence of cardiac arrythmias and CVD hospitalizations increased during the 2016 presidential election (Mefford et al, 2020; Rosman et al, 2021); however, the underlying mechanisms driving these increases, including potentially stress‐related increases in BP, remain unknown. Our findings suggest that population‐level BP, particularly among racial/ethnic minorities, may have increased following the election.…”
Section: Discussionmentioning
confidence: 99%
“…Mefford et al (2020), for example, document an increase in acute cardiovascular disease hospitalizations in California immediately after the 2016 election. Similarly, Rosman et al (2021) show that North Carolina patients with cardiac devices were more likely to experience arrhythmic events during the election. Consistent with the literature examining minority group health, the focus of research documenting these general health effects for the 2016 election suggests a shared sentiment among scholars that many Americans perceived it to be of particularly high stakes and therefore a more stressful, health-threatening experience.…”
Section: Introductionmentioning
confidence: 87%